2018
DOI: 10.17576/jskm-2018-12
|View full text |Cite
|
Sign up to set email alerts
|

The Epidermal Mucus Extract of Clarias Batrachus Inhibits Gram Negative Bacteria Growth

Abstract: Mukus epidermis ikan kini telah dikenalpasti sebagai suatu sumber biologi yang kaya dengan pelbagai bahan bioaktif terutamanya peptida antibakteria. Kajian ini dilakukan bagi mengenal pasti potensi mukus epidermis Clarias batrachus (ikan keli kayu) sebagai sumber kepada bahan antibakteria. Sampel mukus dikumpul dari epidermis C. batrachus dan diekstrak menggunakan kaedah pengekstrakan akueus. Ujian penentuan aktiviti antibakteria ekstrak kasar mukus epidermis C. batrachus dilakukan dengan menggunakan kaedah sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The presence of antimicrobial activity in the ethanol extract of A. paniculata matches with the study of Sahalan et al (2007) who found moderate antibacterial activity against the S. aureus. A. paniculata aqueous extract showed weak antimicrobial activity which is similar to the results of Zaidan et al (2005).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The presence of antimicrobial activity in the ethanol extract of A. paniculata matches with the study of Sahalan et al (2007) who found moderate antibacterial activity against the S. aureus. A. paniculata aqueous extract showed weak antimicrobial activity which is similar to the results of Zaidan et al (2005).…”
Section: Resultssupporting
confidence: 88%
“…The discrepancy in the results obtained in previous literature from the findings in the present study may possibly be due to the difference in the preparation or resuspension of the dried plant extract. Other studies made use of 0.2 % DMSO (Valle et al, 2016) and 10% DMSO (Sahalan et al, 2007) whereas the present study resuspended the pure extract in their respective solvents. It is also possible that the variation in the volume of extracts per disk affects the overall measurement of the inhibition zones since there are studies that made use of 50, 100, and 150 µL per disk (Rajalakshmi & Cathrine, 2016), while this study used 20 µL.…”
Section: Resultsmentioning
confidence: 99%